Psychometric properties of questionnaires to measure social ecological influences in Vietnamese children - Quyen G. To; Danielle Gallegos; Dung V. Do; Hanh TM. Tran; Kien G. To; Lee Wharton; Stewart G. Trost (Sports Medicine and Health Science, 2019)
Physical activity data in primary school-aged children are limited in Vietnam. Although tools to measure social ecological influences on physical activity are validated in English, they are not available in Vietnamese. Due to cultural and contextual differences, their psychometric properties need to be tested. Five scales were translated into Vietnamese and evaluated for internal consistency and test re-test reliability, including self-efficacy, perceived social influences, and beliefs self-administered by students, and parental support for physical activity and parental perceived safety of the neighbourhood, self-administered by parents. Compared to the original scales, two items from the parental perceived neighbourhood safety were removed due to the cultural context. Another item of the self-efficacy scale was also removed as it correlated poorly with the other items in the scale at both administrations. The adjusted scales were found to be reliable and appropriate for use among students and parents to measure social ecological influences on physical activity in the Vietnamese context. Keywords: Physical activity, Exercise, Social ecological influence, Ho Chi Minh city, Elementary school